The Effectiveness of Using AI-Based Chatbots as Virtual Assistants in Programming Learning For Junior High School Students - Imam Dudin; Lisda Ramdhani; Muslimin Muslimin (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
This study aims to measure the effectiveness of using Artificial Intelligence (AI)-based chatbots as virtual assistants in programming learning at SMP. The research method employed was a quasi-experimental design with a pretest-posttest control group. The experimental group used AI-based chatbots, while the control group followed conventional learning. The results showed a significant improvement in the learning outcomes of students in the experimental group compared to the control group. Students' perceptions of chatbot usage also indicated positive responses, particularly in ease of use, learning motivation, and clarity of feedback. The use of chatbots effectively increased student engagement and facilitated adaptive independent learning. Therefore, AI-based chatbots are proven to be an innovative solution to support programming learning in junior high schools. This study contributes to the development of digital learning media relevant to the needs of digital native students.